PENGEMBANGAN MEDIA KOMIK SAINS “PETUALANGAN SI ENERGI” UNTUK MENINGKATKAN PEMAHAMAN KONSEP ENERGI DAN PERUBAHANNYA PADA SISWA KELAS V SEKOLAH DASAR - Ahmad Antoni; Anna Maria Oktaviani; Sastra Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science and social science (IPAS) learning on the topic of energy and its changes in elementary schools is still largely delivered verbally with minimal visual media, causing students to memorize rather than deeply understand the concept. This study aims to develop a learning medium in the form of a science comic titled “Petualangan Si Energi” and to determine its feasibility and effect on students’ understanding of energy and its changes among fifth-grade students at SDN Ragas 2. This study used the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The research subjects were 27 fifth-grade students of SDN Ragas 2 in the 2025/2026 academic year, selected through purposive sampling. Data were collected through expert validation questionnaires, user response questionnaires, and concept-understanding tests (pretest-posttest), then analyzed using the Shapiro-Wilk normality test, Paired Sample t-test, and N-Gain test. The results showed the medium was declared highly feasible, with feasibility percentages of 95% from the material expert, 96.67% from the language expert, and 100% from the media expert. The Paired Sample t-test produced a t-value of 4.087 with a significance of 0.000 (< 0.05), indicating a significant difference between pretest scores (mean 76.63) and posttest scores (mean 77.59). However, the N-Gain value of 0.4 fell into the low category. It can be concluded that the “Petualangan Si Energi” science comic medium is feasible and affects student learning outcomes, although the resulting improvement in concept understanding remains low and should be supported by additional instructional strategies.